A Review of Rice Straw Waste Management in Sidorogo Area from the Perspective of Environmental Law - Mohamad Hafidz Sukanto; Nur Qoilun (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Rice straw remains underutilized in Indonesia despite its considerable potential as a renewable biomass resource for sustainable agriculture. This study examines rice straw waste management in the Sidorogo area from the perspective of environmental law using an empirical legal research design with a descriptive qualitative approach. Primary data were obtained through field observations and semi-structured interviews with rice farmers, while secondary data were collected from legislation and relevant scientific literature. The findings indicate that open burning remains the dominant practice because of limited time for land preparation, inadequate waste-processing technology, and economic considerations. This practice contributes to soil degradation, air pollution, and potential health risks while reflecting limited implementation of environmental regulations. Composting, livestock-feed production, and biomass utilization offer sustainable alternatives that support resource efficiency and reduce environmental impacts. Strengthening environmental law implementation through technological support, farmer education, and institutional collaboration can improve sustainable waste management. Integrating the principles of reduce, reuse, and recycle (3R) with a zero-waste approach provides an effective framework for converting rice straw into valuable agricultural resources while promoting environmental sustainability and rural development.